G251(P) An audit analysing presentation and management of paediatric burns in a pre-hosptial and accident and emergency setting. (27th April 2016) - Matthews, D; Adams, N; Davies, C; Thenabadu, S
Abstract : Aims: Analysis of paediatric burns, including pre-hospital care, presentation and management to the Urgent Care Centre and Accident and Emergency in a district hospital over the course of twelve months for quality improvement. Methods: The audit was undertaken in partnership with consultant medical staff. A data collection form was produced to collect data on all paediatric burn presentations to emergency care services. Mode of presentation, first aid management and pre-hospital care, patient statistics, description and documentation of the incident, including safeguarding protocols, and management in hospital were documented. 145 cases were recorded, over a twelve month period between 1/11/2014–31/10/2015, with a varied distribution in site and severity of burn. Results: 63% of patients carried out some form of first aid prior to hospital attendance, but of these only 8.7% completed the STOP protocol, as recommended on National Burns Awareness day. 15% of patients had a clear description of the burn, including parameters such as size, severity and percentage documented patient notes, but 9.7% of documentation of severity was incorrect, and 46.9% had no documentation. Only 1.4% of patients and their guardians received written guidance after presentation on burn aftercare and prevention with 37.9% receiving no information, written or verbal. Conclusions: The audit revealed three targets of improvement: Public education detailing pre hospital care using the STOP protocol, and after care management. Education of staff, highlighting correct documentation and grading of burns. A policy of provision of written information to patients post presentation. Adoption of these suggestions could affect emergency department attendance and long term prognosis of paediatric burns.